2014
DOI: 10.1186/1472-6874-14-52
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, impacts and medical managements of premenstrual syndrome among female students: cross-sectional study in college of health sciences, Mekelle University, Mekelle, Northern Ethiopia

Abstract: BackgroundPremenstrual syndrome (PMS) is used to describe physical, cognitive, affective, and behavioral symptoms that occur cyclically during the luteal phase of the menstrual cycle and resolve quickly at or within a few days of the onset of menstruation. The primary aim of the study was to assess the prevalence, impacts and medical managements of PMS on female medical students of Mekelle University College of Health Sciences.MethodsA cross-sectional study was conducted among systematically selected female st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
119
7
10

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(168 citation statements)
references
References 12 publications
13
119
7
10
Order By: Relevance
“…The Chisquare analysis also showed that dysmenorrhea is responsible for significant absenteeism from class (X 2 =15; df=2; p=0.001), loss of concentration (X 2 =12.85; df=2; p=0.02), lack of focus on exam (X 2 =7.4; df=2; p=0.025). Different studies agree with our study findings [9,[12][13][14]17,18,[21][22][23][24]. The negative effect of dysmenorrhea comes at its peak when it brings about missed exams and absenteeism.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The Chisquare analysis also showed that dysmenorrhea is responsible for significant absenteeism from class (X 2 =15; df=2; p=0.001), loss of concentration (X 2 =12.85; df=2; p=0.02), lack of focus on exam (X 2 =7.4; df=2; p=0.025). Different studies agree with our study findings [9,[12][13][14]17,18,[21][22][23][24]. The negative effect of dysmenorrhea comes at its peak when it brings about missed exams and absenteeism.…”
Section: Discussionsupporting
confidence: 72%
“…Likewise, the prevalence of premenstrual syndrome (PMS) at Mekelle University college of Health Science reported as 34% [9]. At the same time studies out of the country reported prevalence rate of dysmenorrhea.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…1,6,[10][11][12][13] Os estudos específicos que avaliaram a ocorrência dos sintomas da SPM em acadêmicas de diversos cursos como: enfermagem, fisioterapia, medicina, também relataram a presença dos sintomas supracitados, como é possível visualizar no quadro abaixo (quadro 01). 6,10,12,13,14 Quadro 01: Sintomas da SPM mais frequentes em acadêmicas do ensino superior.…”
Section: Id On Line Multidisciplinary and Psycology Journalunclassified
“…PMS reported in the literature falls into three domains: emotional, physical, and behavioral. The most common emotional and moodrelated symptoms of PMS include depression, irritability, and tension, crying, over sensitivity (hypersensitivity), and mood swings (5).…”
Section: Introductionmentioning
confidence: 99%